A novel application of barycentric coordinates to Lagrange two-way coupled spray calculations. (1st January 2013) - Sinigersky, A.; Koch, R.; Bauer, H-J.
Modern CFD codes make possible the application of two-way coupled Lagrange particle tracking to complex unstructured meshes. State of the art tracking algorithms require the handling of arbitrary-shaped finite volume cells. By developing a new universal module for particle tracking, a novel technique has been introduced: association of the instantaneous particle location to the nearest vertex within a cell. The nearest-node method is then used to store the source terms arising from the spray calculation into vertex-based fields. In this novel method, barycentric coordinates are used for defining the vicinity of a vertex within a cell. The major benefits of this approach are its high computational efficiency and its ability to suppress the influence of mesh skewness on the quality of the results.